Life threatening scorpion sting on adult complicated by: acute toxic myocarditis, cardiogenic shock, pulmonary edema, acute kidney injury and toxic hepatitis: a case report - Filmon Tesfay; Okbu Frezgi; Meron Asheber; Lidia Mussie (Journal of Medical Case Reports)
Abstract Background Occurrence of life-threatening scorpion sting in adults is a rare entity compared with children. Different cases of organ failure following scorpion sting have been reported but complications, such as acute toxic myocarditis, cardiogenic shock, pulmonary edema, acute kidney injury and toxic hepatitis occurring simultaneously in adult patients is exceedingly rare with no prior documented similar report. This case report explores the unique presentation of these complications occurring simultaneously and their management in resource limited setting. Case presentation A 31-year-old Eritrean female came to our emergency room with severe respiratory distress, persistent retching, drenching sweating, generalized pain and unrecordable blood pressure 12 hours after scorpion sting. Electrocardiography revealed signs of diffuse acute myocarditis. The diagnosis of cardiogenic shock and pulmonary edema owing to scorpion sting envenomation was made. The patient also developed acute kidney injury and toxic hepatitis. She recovered well after 10 days of hospital stay and further follow-up, with supportive management and scorpion antivenom. To date, over a period of more than 2 years the patient has no new complaint or complication. Conclusion This case report highlights the clinical novelty of multiorgan failure following scorpion sting in adults. The unique presentation of acute toxic myocarditis, cardiogenic shock, pulmonary edema, acute kidney injury and toxic hepatitis in a 31-year-old female underscores the possibility of scorpion sting causing such life threatening envenomation after delayed presentation. This case contributes to the understanding of atypical presentations of scorpion sting in adults.